Implementation of Mindfulness Techniques in Managing Academic Stress among University Students: Penerapan Teknik Mindfulness untuk Mengelola Stres Akademik pada Mahasiswa Perguruan Tinggi - Anisa Rizki Al Fahmi (Yayasan Cerdas Pedia Indonesia, 2025)
Academic stress significantly impacts university students’ mental health and academic performance. This systematic literature review synthesizes empirical evidence published between 2020 and 2025 on the effectiveness of mindfulness-based interventions for managing academic stress among higher education students. Electronic databases including PubMed, PsycINFO, Google Scholar, and national journal portals were searched for peer-reviewed studies involving structured mindfulness programs and quantitative stress measures. The review included 24 studies comprising randomized controlled trials, quasi-experimental designs, and meta-analyses. Consistent findings indicate that participation in mindfulness programs yields statistically significant reductions in stress, anxiety, and depression, alongside improvements in sleep quality and life satisfaction. Psychological and neurobiological mechanisms underpinning these effects involve enhanced emotion regulation, cognitive reappraisal, decreased amygdala reactivity, and increased self-compassion. Despite methodological heterogeneity and limited longitudinal data in Indonesian contexts, the overall evidence supports integrating mindfulness into student support services. Further research employing rigorous experimental designs and physiological measures is warranted to optimize intervention protocols and assess long-term outcomes.